Narrating In/justice in Angie Thomas’ The Hate U Give - Selma BENHAMADI Khadidja MAHDI (كلية الاداب و اللغات, 2024)
Abstract: This study seeks to analyze the issue of injustice in Angie Thomas’ debut novel, The Hate U Give (2017). The author highlights the ongoing socioeconomic issues faced by African Americans, including the author, such as prejudice, stereotypes, and police brutality, by portraying them through the perspective of the protagonist, Starr Carter. Compounding the already draining experience of having two distinct identities, Starr is subjected to the distressing event of witnessing her childhood companion being fatally shot by a white police officer. Furthermore, she must contend with the detectives and media attempting to conceal the truth and portray the victim as a criminal deserving his demise. Caught in a dilemma between remaining silent and experiencing a sense of betrayal, Starr ultimately resolves to gather herself and employ her voice and activism as a driving force for societal transformation. The thesis employs the Critical Race Theory to examine the portrayal of topics such as intersectionality, double-consciousness, police brutality, and voice of color in the novel, with the aim of reflecting social situations.The main inference from this modest piece of work is that literature is an essential and influential instrument that mirrors the actual world, and that employing one’s voice and activism are the most effective methods to incite the will to resist racial prejudice.
Keywords: Key Words: injustice; police brutality; identity; stereotypes; social change